2018
DOI: 10.1007/s00018-018-2916-7
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine induces cyclooxygenase-2-dependent IL-6 expression in human cardiac fibroblasts

Abstract: Lysophosphatidylcholine (LysoPC) has been shown to induce the expression of inflammatory proteins, including cyclooxygenase-2 (COX-2) and interleukin-6 (IL-6), associated with cardiac fibrosis. Here, we demonstrated that LysoPC-induced COX-2 and IL-6 expression was inhibited by silencing NADPH oxidase 1, 2, 4, 5; p65; and FoxO1 in human cardiac fibroblasts (HCFs). LysoPC-induced IL-6 expression was attenuated by a COX-2 inhibitor. LysoPC-induced responses were mediated via the NADPH oxidase-derived reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…The slices of cardiac apexes were pretreated with the inhibitors for 1 h, and then incubated with LPC for 6 h in Krebs solution (pH 7.4 at 37°C). The homogenates of cardiac apexes were prepared and lysed in a lysis buffer and subjected to Western blot analysis and RT-quantitative (q)PCR, as previously described (5).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The slices of cardiac apexes were pretreated with the inhibitors for 1 h, and then incubated with LPC for 6 h in Krebs solution (pH 7.4 at 37°C). The homogenates of cardiac apexes were prepared and lysed in a lysis buffer and subjected to Western blot analysis and RT-quantitative (q)PCR, as previously described (5).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%
“…The siRNA (100 nM) was added to each well, and then the cells were incubated at 37°C for 6 h. The cells were transferred to DMEM/F-12 medium containing 10% FBS for an additional 6 h, washed twice with PBS, and then maintained in serum-free DMEM/F-12 medium for 24 h before treatment with LPC. (S256D) FoxO1 mutant were cloned into the EcoRV-HindIII site of the pCMV-Tag2B vector, as previously described (5).…”
Section: Transient Transfection With Sirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophosphatidylcholine (LysoPCs) is a proinflammatory factor that leads to atherosclerosis (26). It is an important component of oxidized low-density lipoprotein (ox-LDL) and has a wide range of biological effects (27).…”
Section: Discussionmentioning
confidence: 99%
“…LysoPCs, as proinflammatory phospholipids, can generate superoxide anions in neutrophils 47 . Also, lysoPCs can activate the transcription factor NF-κB to regulate immune and inflammatory pathways and induce interleukin 8 (IL-8) and cyclooxygenase-2-dependent interleukin 6 (IL-6) expression and secretion 48,49 . Previous studies demonstrated higher serum IL-6 and IL-8 levels in FM patients than healthy controls 50,51 .…”
Section: Discussionmentioning
confidence: 99%